Identity Politics and Voting Behavior among Indigenous Communities: The Case of the Tuho Ulumanda Community in the 2009–2024 Legislative Elections - Gunawan Gunawan (Journal of Contemporary Local Politics, 2025)
This study examines voter behavior in the Tuho Ulumanda indigenous community across Indonesia’s 2009–2024 legislative elections, a period marked by rapid political and media change that is reshaping electoral decision-making in rural and customary settings. Drawing on qualitative decision-study data from Ulumanda, Majene Regency (West Sulawesi), the paper analyzes how cultural norms and customary law interact with newer influences such as campaign strategies, social media exposure, political education, socioeconomic conditions, and locally salient issues. The study’s novelty lies in tracing these interacting drivers longitudinally across multiple election cycles within an indigenous community, rather than treating tradition and modern campaigning as separate explanations. Findings show that voting choices remain strongly structured by cultural beliefs and the authority of local leaders, even as external political communication expands. The research also identifies emerging tensions that hinder the reproduction of Tuho Ulumanda customary values, particularly regarding family obligations and adherence to customary law, which in turn shape electoral preferences and participation. By clarifying the mechanisms linking customary authority to contemporary electoral dynamics, the study contributes evidence for more context-sensitive voter education and democratic engagement in indigenous communities.